Internet Media Literacy for UPN “Veteran” East Java Students - Diana Hertati; Yudiana Indriastuti; Irwan Dwi Arianto (Nusantara Science and Technology Proceedings)
Internet with the development of communication technology is increasingly increasing, closer and increasingly pamper its users with various information. A lot of the variety of information on the internet can be a benefit too can be a problem. The Internet can be very difficult to avoid, especially when the blank spot area is running low. This study illustrates how internet usage among students in relation with internet media literacy to the understanding of whether students are critical with media content used or consumed. The Campus of UPN Veteran of East Java as State Defense College course in implementation is to identify AGHT information which is not inevitable anymore. Student UPN Veteran of East Java as Surabaya citizen who recently proclaimed as Cyber City certainly have to clean up in this case. Cyber City brings the consequences of more complete internet network in this city. Collecting data through participatory observation, in-depth interviews, focus group discussions and literature to explore more deeply how the use of the Internet among students UPN Veteran of East Java.